Experiences of healthcare professionals in the community dealing with the spiritual needs of children and young people with life-threatening and life-limiting conditions and their families: report of a workshop. Issue 3 (27th June 2013) - Llewellyn, Henry; Jones, Louise; Kelly, Paula; Barnes, Jeanette; O'Gorman, Bernadette; Craig, Finella; Bluebond-Langner, Myra
Abstract : Objective: We sought to understand how healthcare professionals (HCP) conceptualise spirituality among seriously ill children and young people (CYP) and their families, and their experiences in dealing with spiritual issues that emerge in practice. Method: We analysed thematically presentations and small group discussions with HCP that took place as part of a day-long workshop exploring the place of spirituality in paediatric healthcare. Results: (1) HCP conceptualised spirituality as highly individualised searches for meaning, hope and connectedness to self, others and the world. They saw spirituality within a developmental context. (2) HCP described spiritual concerns that were tied to their own conceptualisations of spirituality, centring on ideas of loss, including loss of hope or meaning. (3) HCP approached spiritual concerns of CYP and families by 'being there' and supporting spiritual enquiry. (4) Challenges to their work included managing hopes of CYP and families in the face of poor prognoses, discussions about miracles and issues with their own faith. Spiritual care was seen as different to other areas of care which HCP felt had a greater prescription in delivery. Conclusions: The findings underscore the complexity of spirituality in times of illness and the challenges faced in its management. HCP should be alerted to the myriad ways spirituality emerges in serious illness and opportunities for developing confidence in attending to spiritual issues with CYP and families through training. Research should explore with patients, families and HCP how tensions among CYP, autonomy, the maintenance of hope and miracle beliefs are best approached within care.